Small firms’ motivations in offering apprenticeship training in Switzerland - Baumeler, Carmen [Verfasser]; Lamamra, Nadia [Verfasser] (My University, 2024)
„This paper aims to determine what motivates small firms to offer apprenticeship training. The current state of research provides various indications. While research focusing on the specificity of small firms identifies the important role of the owner and their personality, values, attitudes and experiences, economic research mainly refers to the explanatory factor of profitable cost-benefit relationships in apprenticeship training. Finally, research on the institutional embeddedness of firms points to the importance of institutional framework conditions. Our contribution links these three usually unrelated research perspectives and focuses on Switzerland as a collective skill formation system. We asked heads (owners, managers, or other collaborators) of small firms who make autonomous decisions regarding personnel and budget issues about their motivations in offering apprenticeship training using qualitative interviews. The results show that, at the individual, organisational, and societal levels, different motivations influence the provision of training positions. Furthermore, within small companies, we identified heterogeneous motivational configurations. In conclusion, if the participation of small firms in the provision of apprenticeship places is to be promoted, their heterogeneity and motivations in doing so must be addressed at various levels.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.2.1 KMU, Klein- und Mittlere Unternehmen; S 3.2 Unternehmen und Behörden; 370; Klein- und Mittelbetrieb; Ausbildungsverhalten; Einflussfaktor; Kosten-Nutzen-Relation; Interview; Schweiz